2014
DOI: 10.1039/c3lc51419f
|View full text |Cite
|
Sign up to set email alerts
|

Trapping self-propelled micromotors with microfabricated chevron and heart-shaped chips

Abstract: Catalytic micromotors are trapped in microfluidic chips containing chevron and heart-shaped PDMS structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…35 This ratchet effect in effectively two-dimensional systems becomes more pronounced for large perimeter-to-surface ratios and therefore lets us envisage the design and manufacture of miniaturized devices to control the cell dynamics as well as the artificial microswimmer dynamics for selection, testing, concentration, separation [36][37][38] or trapping. 39,40 In this work, we demonstrate that, by properly texturing the sample borders, it is possible to tune the relative density of cells in the interior of a shallow chamber by diminishing the sperm density at its perimeter. In addition, we provide further insights on the motility of human sperm cells confined between two surfaces separated by $25 lm, a distance shorter than their own length, $60 lm.…”
mentioning
confidence: 78%
“…35 This ratchet effect in effectively two-dimensional systems becomes more pronounced for large perimeter-to-surface ratios and therefore lets us envisage the design and manufacture of miniaturized devices to control the cell dynamics as well as the artificial microswimmer dynamics for selection, testing, concentration, separation [36][37][38] or trapping. 39,40 In this work, we demonstrate that, by properly texturing the sample borders, it is possible to tune the relative density of cells in the interior of a shallow chamber by diminishing the sperm density at its perimeter. In addition, we provide further insights on the motility of human sperm cells confined between two surfaces separated by $25 lm, a distance shorter than their own length, $60 lm.…”
mentioning
confidence: 78%
“…Restrepo-PØrez et al demonstrated the trapping of micromotors and the elimination of the need for external energy sources to control their motion. [169] The technique relies solely on steric boundaries present on microfluidic chips containing chevron and heart-shape engineered structures (Figure 17 B). Chevron-shaped structures with angles from 40 to 1408 were fabricated from PDMS, and showed a higher trapping efficiency than smaller angles, as previously predicted theoretically.…”
Section: Microchips and Physical Boundariesmentioning
confidence: 99%
“…Active matter itself has been intensely explored over the last years, both for living systems as bacteria [4], spermatozoa [5] and mammals [6,7] or is system of artificial microswimmers [8][9][10][11][12][13] with various propulsion mechanisms [14][15][16][17] and a plethora of nonequilibrium pattern formation phenomena were discovered [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. At fixed system boundaries active system show distinct clustering and trapping behaviour [34][35][36][37][38][39][40][41][42][43][44][45] and can be expoited to * kaiser@thphy.uni-duesseldorf.de steer the motion of microrotors and microcarriers [46][47][48] of fixed shape.…”
Section: Introductionmentioning
confidence: 99%